Road Map for Nanocrystal Based Infrared Photodetectors - Livache, Clément; Martinez, Bertille; Goubet, Nicolas; Ramade, Julien; Lhuillier, Emmanuel (Frontiers in Chemistry, 2018)
Infrared (IR) sensors based on epitaxially grown semiconductors face two main challenges which are their prohibitive cost and the difficulty to rise the operating temperature. The quest for alternative technologies which will tackle these two difficulties requires the development of new IR active materials. Over the past decade, significant progresses have been achieved. In this perspective, we summarize the current state of the art relative to nanocrystal based IR sensing and stress the main materials, devices and industrial challenges which will have to be addressed over the 5 next years.